O4 HLA-typing as a cost effective screening test for coeliac disease in children with down syndrome. (12th September 2022) - Lewis, Timothy; Yates, Jill; Mitchell, Rod; Turner, David; Chambers, Hattie; Sumner, Claire; Clegg, Sarah; Gillett, Peter
Abstract : Background: Children with Down Syndrome (DS) are at increased risk of coeliac disease (CD). Current screening practice in DS includes tissue transglutaminase IgA (TGA-IgA) serology. There is no standard UK guidance on frequency of serology testing or inclusion of HLA-typing for CD predisposing antigens, DQ2 and DQ8. HLA testing can be performed before gluten exposure and to coincide with other routine investigations. A negative DQ2/DQ8 type means patients do not require further coeliac screening. A positive DQ2/DQ8 type allows risk stratification of patients. We explored the cost-effectiveness and family acceptance of a screening strategy which involved both serology and HLA-typing of children with DS. Methods: Children in Lothian with DS were screened for coeliac disease using HLA-DQ2/DQ8 typing and IgA-TGA serology as part of an established programme following publication of 2012/2013 guidelines from ESPGHAN/BSPGHAN, seen as 'standard of care'. Data collected included the frequency of HLA DQ2/DQ8, assessed with serology testing. Existing patients with CD were identified as part of analysis of the Lothian DS cohort. The cost of HLA haplotyping in NHS Lothian is £31.16, TGA-IgA £15.92 and Total IgA £3.66. Results: 127 of 176 children with DS (73%) were screened using DQ typing. One family did not consent to DQ typing or serology. Overall, DQ2/DQ8 antigens were identified in 75 (59%) and 52 (41%) were negative . Patients with known CD who were tested (9 out of 12) were all DQ2/DQ8 positive. TGA-IgA serology was performed in 143 of 176 (82%) with a median number of tests per patient of 1. Compared to only TGA-IgA screening, there was an estimated saving of £3.37 per patient. Conclusions: A significant minority (41%) of DS children are negative for CD-predisposing HLA genotypes and are therefore excluded from further screening. DQ typing is a cost-effective CD screening strategy and was generally well received. In addition to the modest saving in laboratory costs, there will be further benefits from reduction in frequency of serology screening: reduced hidden costs within phlebotomy, diminished pressure on health services, and savings to families of both expense and time. A negative DQ type also excludes a significant condition for families dealing with other complex health issues, the benefit of which cannot be underestimated. The Down Syndrome Medical Interest Group in the UK are considering the adoption of such a strategy.